The disconsolation of philosophy: May Sinclair, modernism, and disability. Issue 4 (2nd April 2020) - Sessions, Gabriel
ABSTRACT: This article presents a new comparison of modernist literature and early twentieth-century philosophy as historically contemporaneous and mutually citational practices. Both offer a critique of the universality of Western reason and the supposed positivity of the natural sciences by reinterpreting the pathological types and identities these sciences provide, allowing subjects who fit such identities to construct new theories that rationalise and adapt to their vulnerability to biopolitical power-knowledge. Hence, philosophy, as a modern elegiac mode, rehabilitates 'disconsolation', rather than offering a recuperative 'consolation', as it might have in pre-modern times. This article illustrates this point through the archive of the British modernist author May Sinclair. Sinclair's practice as a philosopher, often deemed ancillary to her fiction and essays, sheds new light on her critical illegibility, if we understand how it is motivated by Sinclair's bodily experience of genetic illness. Philosophy allows Sinclair's fiction to transform concepts of agency and biopolitical determinism to make her vulnerability to scientific laws a pleasurable virtue. Translating these ideas to the level of form as well, Sinclair's novels represent a modernist reaction against the clinical narratorial gaze of literary naturalism, rewriting its experimental protocols from the perspective of the sick body itself.